HUBUNGAN PENANAMAN NILAI RUKUN KEPADA ANAK TERHADAP PERILAKU RUKUN TINGKAT SMP - Rosada, Ulfa Danni; Effendi, Kusno; Wahyudi, Amien (Universitas Muria Kudus, 2017)
The purpose of the research is want to get a about the relationship by parents to take great care of planting the value of a child at the public junior high schools all the kabupaten bantul students. The method in this research is quantitative research method. Data Collection Techniques using questionnaires implantation on the pillars. In the research conducted, the technique used for data collection is a questionnaire. Total item questionnaire in the form of two alternative answers (yes and no), compiled 45 items. The research was conducted in four (4) locations in Bantul, as follows: (a) The area of Bantul North, (b) Region Bantul West, (c) The area of Bantul South, (d) The area of Bantul East, (e) The area of Bantul Central. Sampling technique is non-random sampling. Data analysis techniques using Product Moment Correlation. The correlation between the value of the behavior of harmony with the value of planting along well with p = 0.71 and p <0.05 means there is no correlation between the value of the pillars of the behavior of students with grades of planting the pillars by the parents to the student. When seen from the value of p 0.71 p> 0.05 so that it can be concluded that there is no relationship between the implantation on the pillar by the parents to the students of the pillars of student behavior.